Peningkatkan Layanan Bimbingan Konseling Siswa SMP Negeri 1 Mempawah Hilir Melalui Media Audiovisual - Ratnawati, Rr. Eka (Universitas Tanjungpura, 2024)
Audiovisual media play a crucial and relevant role in guidance and counseling services for junior high school students in line with technological advancements in education. This study aims to assess the extent of the impact of audiovisual media on counseling and guidance services. The research methodology combines an experimental research design with a quantitative approach. This was achieved through the use of questionnaires administered twice: once before the test (pretest) and once after the use of audiovisual materials (posttest). A total of 25 eighth-grade students from SMP Negeri 1 Mempawah Hilir were selected as the sample for this study. The pretest score was 0.192 and the posttest score was 0.188, resulting in significant data values consistent with the findings of the hypothesis calculations conducted using the Normality Test. Given that the results exceeded the significance level of Î± = 0.05, the data were determined to be normally distributed. Based on the findings from the Paired Sample T-Test, which yielded a significant (2-tailed) result of 0.00 and an Î± value of 0.05, the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted because the significant (2-tailed) value of 0.00 is less than 0.05 (0.00 0.05). Therefore, it can be concluded that SMP Negeri 1 Mempawah Hilir utilizes audiovisual media in significantly different ways to enhance student counseling and guidance services.